Analisa Pengaruh Peranan Pemimpin Terhadap Kepuasan Kerja Melalui Pengembangan Karir dan Disiplin Kerja Karyawan Bagian Marketing PT. Bank Rakyat Indonesia (Persero) tbk Kantor Cabang Malang Martadinata - I Gusti Gede Narung (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
This study will examine four variables, specifically the role of leaders, career developmnet, work discipline and job satisfaction as intervening variables. Respondents in this study were permanent employees or marketing departement in PT. Bank Rakyat Indonesia (Persero) Tbk: Malang Martadinata Branch Office, a number of samples of this research are 45 employees. The analytical technic that is used in this study are descriptive and multiple linier regression for the formation in a structural equation model which made by the researcher. This research used a quantitative approach to explain in the influence between research variables. The results of this study found that the role of the leader showed insignificant indications on employee job satisfaction, but had a significant imfact if metiated by career development and employee work discipline.